Understanding Farmers and Herdsmen Conflict, The case of Crop Farmers and Fulani Herders In the Asante Akim North District - Kyei-Poakwah, K. (University of Ghana, 2018)
Farmers and herdsmen have co-existed for centuries. Nonetheless, as the world population increases, migration induced by climate change and the increasing prevalent scarcity of resources, farmers-herdsmen relationship has tragically experienced a paradigm shift of co-existence to fierce competition over limited resources. The primary objective of this study is to engage the gap in the literature as to why farmers and herdsmen conflict in Ghana have become protracted, increasingly violent and widespread across the country. This conflict after years of attempts by successful Ghanaian government to resolve it, continues to be insuperable and consequently detrimental to Ghana development agenda particularly in the Agricultural and livestock industry. This study centres on the case study of the Asante Akim North District in Ghana. This district has experienced the highest cases of farmers-herdsmen conflict within the country. The study employed qualitative methodology and methods of data collection, with the use of interviews, observation and a review of documents provided by key stakeholders. The study found out that the clashes between the Fulani who are widely regarded as ‘foreign invaders’ and farmers stems from the competitive use of land for their respective agrarian livelihoods. Furthermore, it is identified that issues such as the influence of so-called ‘Big Men’ with extensive political network; the economies of agrarian livelihoods and the poor land distribution policy of the chiefs are the pertinent issues underlying farmers and herdsmen conflicts. This thesis recommends, that in order to avert a conflagration between farmers and herders the solution depends on public policy on‘Cattle Colonies’ and Early Warning Mechanisms which ought to be implemented by the relevant stakeholders without any measure of political interference.
MPhil.
Keywords: Crop Farmers; Fulani Herders; Asante Akim North; Conflict